Bio-inspired catalyst-driven efficient CO2 capture and subsequent mineralization in aqueous media under practical conditions - B. Rajeshwaree; Anwesha Banerjee; Abhishek Saini; Piyali Majumder; Vikram Vishal; Arnab Dutta (Carbon Capture Science & Technology)
Efficient carbon management and the successful implementation of innovative technologies are a necessity for environmental mitigation and the realization of a sustainable circular economy. Current carbon dioxide removal (CDR) and CO2 capture and storage (CCS) technologies fail to meet the gigatonne-level CO2 removal targets, lack profitability, and thus are not widely adopted/retrofitted in the current industrial settings. To address these issues, unique alternative solutions are required that possess the versatility for application in various CO2-emitting industries, have economic viability, and do not cause secondary pollution effects. Our pursuit in this regard led to the development of a catalyst C1, inspired by the architectural design of the Carbonic anhydrase enzyme, where a Zn (II) ion is bound tetrahedrally at the N3-primary coordination site and a peripheral ethereal O3-site which functioned as the outer coordination sphere (OCS). This promoted the facile generation of the potent Zn-OH– motif in near-neutral media for rapid hydrolysis of CO2 in aqueous solution to carbonate and bicarbonate ions. Mineralization of this captured CO2 was performed with the appropriate addition of Ca(II) ions leading to the formation of pure CaCO3. Practical application and industrial relevance were established with CO2 capture and mineralization experiments performed in seawater, flue-gas mixture with 15 % (v/v) CO2, and air containing only 0.04 % (v/v) CO2 in a separate set of experiments. The kinetic parameters and biomimetic nature of the metal complex C1 were confirmed through detailed pNPA hydrolysis studies. Our results indicate that bio-inspired catalysts can be a cost-effective, viable solution for mass-scale carbon mitigation and management strategy using only environmentally benign resources.